Light pollution in Maribor - Žiberna, Igor (Journal for Geography, 2016)
Light pollution represents a new form of environmental pollution which is the result of excessive use of artificial lighting at night. The light pollution is the emission of light from the light sources that increases the natural illumination of the environment. Light pollution causes to human vision distraction illumination and a feeling of glare, it threatens the safety in traffic due to the glare, endangers the natural balance, disrupts the professional or hobby an astronomical observation and unnecessarily consumes power. In article are presented results of measurements of the light pollution, with the Sky Quality Metres in the area of the city of Maribor. Presented are also the results of the analyses of the light pollution roses and resources consumed for public lighting in the area of the municipality of Maribor.
Keywords: light pollution; Maribor; environmental protection